Manajemen Karir dan Pengembangan Diri Mahasiswa: Perbandingan Strategi pada Jalur Masuk Perguruan Tinggi - Bahar, Andrizal; Giatman, M; Maksum, Hasan (Universitas Negeri Padang, 2024)
The aim of this study is to compare career management strategies and levels of self-development among automotive engineering students at FT UNP who enrolled in 2019, particularly at the fourth stage of their studies. The research sample comprises 60 students, with 20 students from each admission path: SNMPTN, SBMPTN, and Independent Selection. The analysis employs ANOVA to address two research hypotheses regarding the differences in career management strategies and levels of self-development among the three admission paths. The results of the study significantly support the first hypothesis, indicating a meaningful difference in career management strategies among students admitted through SNMPTN, SBMPTN, and Independent Selection. Similarly, the second hypothesis is also confirmed, demonstrating a significant difference in the level of self-development among students from the three admission paths. This research provides valuable insights into how automotive engineering students navigate their careers and self-development through various admission paths. The practical implications of the study can offer guidance to academic institutions and stakeholders to enhance the effectiveness of career management and student self-development, taking into account the diverse characteristics and needs of students from different admission paths.